Research on ways to attract foreign patients to a Korean medicine clinic: a retrospective 2024 case study from Seoul - Jeong Hyeon Kim; Serin Lee; Mijoo Kim; Seung Hwan Lee; Jeong-Su Park (Frontiers in Medicine)
IntroductionThis study aimed to analyze the clinical characteristics and treatment patterns of foreign patients visiting a single Korean medicine clinic to identify strategies for improving TKM-based medical tourism in South Korea.MethodsThis study retrospectively reviewed the electronic medical records of 318 foreign outpatients who visited Tong-In Korean Medicine Clinic in Seoul from January to December 2024. Data on patient demographics, nationality, number of visits, treatment modalities, diagnoses, and herbal medicine prescriptions were collected and analyzed.ResultsThree Hundred and Eighteen foreign patients visited a single Korean medicine clinic. 68.9% were female and 31.1% were male, with the majority in their 20s and 30s. Patients originated from 51 countries, with the highest proportions from the United States (31.45%), France (12.27%), and Singapore (8.49%). Most visits occurred in May and September. The most common type of case was musculoskeletal disorders (73, 9%). A total of 108 patients (34.0%) received combined modality treatment, with 88 patients (81.5%) receiving both acupuncture and internal medicine services. Herbal medicine was prescribed to 53.8% of patients, who took it for an average of 36.66 days per person. Pills were preferred over decoctions, with over twice as many patients taking pills (188) than decoctions (80).DiscussionThe result of this study suggests that TKM-based medical tourism has a meaning in the realm of treating musculoskeletal disorders but also in internal medicine care. Also, this is the first post-COVID-19 study analyzing a TKM clinic in the context of medical tourism globalization. The growing demand for internal medicine services along with long-term herbal medicine use highlights the importance of integrated and personalized TKM medical programs to enhance the global competitiveness of TKM.